2016
DOI: 10.3892/ol.2016.4495
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the WW domain-containing oxidoreductase in human hematopoietic malignancies

Abstract: Abstract. The role of the WW domain-containing oxidoreductase (WWOX) gene in multiple types of solid human cancers has been documented extensively thus far. Recently, we investigated the in vitro effects of WWOX overexpression and observed marked growth arrest in human leukemia cells; however, the clinical characterization of WWOX in leukemia remains poorly investigated. The present study evaluated the WWOX expression profiles of 182 patients with leukemia of different types and 5 leukemic cell lines, using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…A number of studies have contributed to the description of the role of this gene in leukemic malignancies. Luo et al [ 33 ] found that the expression of the WWOX mRNA and protein is significantly reduced or absent in cases of leukemia and their cell lines in comparison with the controls, which is consistent with the findings of Cui et al [ 34 ], who evaluated patients diagnosed with different types of leukemia.…”
Section: Discussionsupporting
confidence: 80%
“…A number of studies have contributed to the description of the role of this gene in leukemic malignancies. Luo et al [ 33 ] found that the expression of the WWOX mRNA and protein is significantly reduced or absent in cases of leukemia and their cell lines in comparison with the controls, which is consistent with the findings of Cui et al [ 34 ], who evaluated patients diagnosed with different types of leukemia.…”
Section: Discussionsupporting
confidence: 80%
“…Li suggests that WWOX may have potential clinical implications in bladder cancer therapy 6. In a study of 182 patients with leukemia of different types, Luo suggests WWOX has potential to be a good biomarker or predictor for leukemia therapy 7. WWOX can suppress stem cell properties in cancer stem cells, including self-renewal ability, differentiation potential, in vivo tumorigenic capability, high-level expression of stem cell genes and multidrug resistance 5…”
Section: Introductionmentioning
confidence: 99%
“…Luo ve ark. WWOX ifadesinin farklı lösemi tiplerinde normal kontrollere kıyasla azaldığını veya kaybolduğunu göstermişlerdir23 . Chen ve ark.…”
unclassified